PENGGUNAAN MEDIA SANDPAPER LETTERS (SPL) UNTUK MENINGKATKAN KETERAMPILAN MENULIS PADA SISWA KELAS 1 SD - Dewi, Galuh Kartika; Dwi Cahya Salsabila (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to introduce the alphabet by allowing students to experience letter shapes and learn the correct way of writing using sandpaper letters (SPL) media, which serves to improve the writing skills of 1st-grade elementary school students. The research method employed is Classroom Action Research (CAR) conducted in the 1st grade of SDN Lemah Putro with 20 students. Data were collected through written tests and observations. The data analysis technique involved comparing the percentage of learning mastery and observing student learning activities using SPL media across Cycles I and II. The results showed that during the pre-action stage, student mastery was 20% (4 students). In Cycle I, mastery of cursive writing increased to 50% (10 students) in the pre-test and 60% (12 students) in the post-test, with student activity reaching 75% in the